NILAI ESTETIS TIDI LO BITU’O (STUDI KASUS DI SANGGAR TUMULA GORONTALO) - Nazly Friena S. Pakaya; Riana Diah Sitharesmi; Rahmawati Ohi; Nurlia Djafar; Mimy Astuty Pulukadang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted due to the beauty of one of Gorontalo’s traditional art forms. The type of art referred to is tidi, meaning “dance.” Among the eight types of tidi in Gorontalo, Tidi Lo Bitu’o stands out as particularly captivating. This study addresses two main problems: identifying the components of Tidi Lo Bitu’o and examining how its structure conveys aesthetic value. The study employed a qualitative case study approach, focusing on analyzing the dance performances of the Tumula Studio dancers, using Janet Adshead’s theoretical framework as presented in Riana Diah Sitharesmi’s book, alongside A.A.M. Djelantik’s theory of aesthetics. The study aims to describe Tidi Lo Bitu’o’s components and interpret the aesthetic values embodied within its structure. The findings reveal that the components of Tidi Lo Bitu’o include movements, dancers, visual set elements (stage setting, lighting, costumes, facial makeup, hair styling, and props), and aural elements in the form of accompanying music, featuring lyrics sung in the Gorontalo language accompanied by rebana and koloko’o instruments. Regarding aesthetic values based on A.A.M. Djelantik’s framework, three key aspects were identified: unity, demonstrated through the relationship among movements, dancers, visual set, and aural elements; emphasis, found in the opening sequence through the music, dancers with salenthangi props, and the core section where the bitu’o prop is actively used along with the music; and balance or harmony, observed through the blending elements of Tidi Lo Bitu’o and the relationship between the two props used, salenthangi and senthangi.